Aging in place: community-based services and resources in residential settings among older adults. Issue 1 (4th May 2017) - Ewen, Heidi H.; Emerson, Kerstin G.; Washington, Tiffany R.; Carswell, Andrew T.; Smith, Matthew Lee
ABSTRACT: One key component to facilitate older adults' ability to remain independent and age in place is the provision of formal services in their community. However, elder-targeted services are lacking for many older adults depending on their area of residence. This study explores the disparity of formal service utilization by residence among adults aged 50 years and older ( N  = 672). We compared elders living in the community, elders living in service-poor housing (e.g., subsidized public housing), and elders living in service-rich housing (e.g., continuing care retirement community). Results suggest that older adults living in service-poor housing have greater physical and mental health concerns compared to those in service-rich housing. Those in service-poor housing also have less social and economic resources. These factors may decrease the ability to age in place if residents cannot afford services or cannot navigate the system. Opportunities and challenges based on these data are discussed.